(2S,4S)-3-Acryloyl-6-oxo-2-phenylperhydropyrimidine-4-carboxylic acid - Kundu, S.K.; Mahindaratne, M.P.D.; Quinones, B.; Negrete, G.R.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
In the title compound, C(14)H(14)N(2)O(4), the central six-membered ring adopts a twisted boat conformation with the phenyl substituent occupying an orthogonal position [dihedral angle = 86.88 (11)degrees]. In the crystal, molecules are linked by carboxylic acid-carbonyl O-H center dot center dot center dot O and amide-carbonyl N-H center dot center dot center dot O hydrogen bonds, forming a three-dimensional network.